2021
DOI: 10.3389/fpubh.2021.758457
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exposure to Natural and Built Environments on Positive and Negative Affect: A Systematic Review and Meta-Analysis

Abstract: There is increasing evidence that the natural environment provides substantial benefits to human emotional well-being. The current study synthesized this body of research using the meta-analysis and assessed the positive and negative effects of exposure to both the natural and built environments. We searched four databases and 20 studies were included in the review. The meta-analysis results showed the most convincing evidence that exposure to the natural environment could increase positive affect (standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…[ 10 , 11 , 12 ]. Indeed, a meta-analysis study showed that exposure to natural environments was associated with a moderate increase in positive affect and a smaller, yet consistent, decrease in negative affect relative to comparison conditions [ 13 , 14 ]. Additionally, lower immune activation was observed following social stress in rural compared to urban participants raised with regular or no animal contact, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 , 11 , 12 ]. Indeed, a meta-analysis study showed that exposure to natural environments was associated with a moderate increase in positive affect and a smaller, yet consistent, decrease in negative affect relative to comparison conditions [ 13 , 14 ]. Additionally, lower immune activation was observed following social stress in rural compared to urban participants raised with regular or no animal contact, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies discover that greenery is vital in improving caregivers' life quality, enhancing their care quality, and further promoting frail older adults' health ( 13 , 60 ). Green spaces also promote the quality of physical activities, such as cycling, hiking and tai chi, and positively reinforce more “green activities” ( 61 , 62 ). Policymakers in future urban planning can involve environmental greenery and transit for sustainable service delivery and community development.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to natural environments increases positive affect and decreases negative affect [ 120 , 121 ]…”
Section: Therapeutic Interior Design For People With Chronic Diseasesmentioning
confidence: 99%